Method for preparing nickel-manganese modified carbon-based assembly material based on lignin and energy storage application of nickel-manganese modified carbon-based assembly material

Ni-doped carbon dots were prepared by mixing lignin with nitric acid and hydrothermal reaction with nickel chloride hexahydrate, and Mn-N-C materials were formed by manganese nitrogen doping and carbonization treatment, and Ni-CDs were finally treated by sonication. Loading to Mn-N-C materials, a carbon-based assembly material with nickel-manganese modification was prepared, which solved the problems of low raw material utilization, environmental pollution and insufficient energy storage performance in the existing technology, and achieved efficient and environmentally friendly energy storage. Material preparation.

CN119409165APending Publication Date: 2025-02-11WUHAN UNIV OF SCI & TECH
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411534368.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-31
Publication Date
2025-02-11

AI Technical Summary

Technical Problem

The methods for preparing carbon dots in the prior art have problems such as low raw material utilization, environmental pollution and insufficient energy storage performance. In particular, the research on lignin carbon dots is mainly focused on blue fluorescence emission, which hinders its widespread application.

Method used

By mixing lignin with nitric acid and sonicating, nitric acid-treated lignin is obtained, and then hydrothermal reaction is carried out with nickel chloride hexahydrate to obtain nickel-doped carbon dots (Ni-CDs). Next, the filter slag is doped and carbonized to form a Mn-N-C material, and Ni-CDs are loaded onto the Mn-N-C material by sonication to prepare a nickel-manganese-modified carbon-based assembly material.

Benefits of technology

The all-round utilization of lignin is realized, and the nickel-manganese modified carbon-based assembly material has excellent energy storage performance, is suitable for water-based zinc ion batteries, and is environmentally friendly, solving the energy density of traditional carbon materials in energy storage. and the problem of low power density.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure HDA0005111199610000011
    Figure HDA0005111199610000011
  • Figure HDA0005111199610000012
    Figure HDA0005111199610000012
  • Figure HDA0005111199610000013
    Figure HDA0005111199610000013
Patent Text Reader

Abstract

The invention discloses a method for preparing a nickel-manganese modified carbon-based assembly material based on lignin. The method comprises the following steps: (1) treating lignin with nitric acid to realize lignin cracking and nitrogen doping; (2) uniformly mixing the lignin treated by nitric acid, nickel chloride hexahydrate and solvent water, carrying out hydrothermal reaction to obtain filtrate and filter residues, and dialyzing and freeze-drying the filtrate to obtain nickel-doped carbon dots; (3) mixing the obtained filter residue with cyanuric acid, melamine, manganese sulfate monohydrate and water, carrying out hydrothermal reaction to realize metal manganese doping, and then carrying out carbonization treatment in a tubular furnace to obtain a manganese-nitrogen doped carbon material; and (4) mixing the manganese-nitrogen-doped carbon material and the nickel-doped carbon dots with water, stirring and performing ultrasonic treatment to obtain the nickel-doped carbon dot composite manganese-nitrogen-doped carbon material, namely the nickel-manganese modified carbon-based assembly material. According to the invention, the comprehensive utilization of lignin is fully realized, the preparation process is green and environment-friendly, and the nickel-manganese modified carbon-based assembly material for the aqueous zinc ion battery is prepared and has excellent energy storage performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of biomass nanomaterials and energy storage technology, and more specifically, to a method for preparing a nickel-manganese modified carbon-based assembly material based on lignin and its energy storage application. Background Art

[0002] Carbon dots (CDs) are zero-dimensional materials with a size below 10 nm, which have attracted wide attention for their photoluminescence and catalytic properties. Compared with traditional carbon materials, CDs have abundant edge positions and surface functional groups, have strong adsorption capacity for electrolyte ions, and provide abundant active sites for improving electrochemical performance. As a potential candidate material for energy storage devices, CDs have attracted wide attention in the field of energy storage.

[0003] In recent years, lignin has been favored by more and more researchers as a precursor for preparing CDs. However, the structure of lignin is complex and consists of multiple connecting bonds and functional groups, which makes it difficult to depolymerize and not easy to directly synthesize CDs. Moreover, most of the existing methods for preparing CDs do not conform to the concept of sustainable development. Generally, CDs are prepared by hydrothermal reaction of raw materials, and the yield is very low. Not only does it greatly reduce the utilization rate of raw materials, but the residue left by the hydrothermal reaction is directly discarded, which will cause certain damage to the environment. In particular, the current research on lignin carbon dots mainly focuses on blue fluorescence emission, which greatly hinders the widespread application of CDs. In addition, the current application of carbon materials in energy storage has the disadvantages of low energy density and power density, which cannot meet the needs of real life. Summary of the invention

[0004] The technical problem to be solved by the present invention is to provide a method for preparing a nickel-manganese modified carbon-based assembly material based on lignin in response to the deficiencies in the above-mentioned prior art, which fully realizes the all-round utilization of lignin, and the preparation process is green and environmentally friendly. The prepared nickel-manganese modified carbon-based assembly material can be used for aqueous zinc ion batteries and has excellent energy storage performance.

[0005] The technical solution adopted by the present invention to solve the above-mentioned problems is:

[0006] A method for preparing a nickel-manganese modified carbon-based assembly material based on lignin comprises the following steps:

[0007] (1) mixing lignin with water, then dropping nitric acid into the mixture and mixing, ultrasonically treating the mixture, filtering the mixture, washing the mixture with deionized water, and freeze-drying the mixture to obtain nitric acid-treated lignin;

[0008] (2) mixing the lignin treated with nitric acid obtained in step (1) and nickel chloride hexahydrate with water, and then performing a hydrothermal reaction; after the hydrothermal reaction is completed, solid-liquid separation is performed to obtain a filtrate and a filter residue; after filtering the filtrate to remove insoluble matter, the filtrate is dialyzed and freeze-dried to obtain nickel-doped carbon dots (Ni-CDs); and the filter residue is dried for standby use;

[0009] (3) mixing the filter residue obtained in step (2) with cyanuric acid, melamine, manganese sulfate monohydrate and water, and performing a hydrothermal reaction to achieve metallic manganese doping. After the reaction is completed, the solid is collected, dried and transferred to a tubular furnace for carbonization treatment to obtain a manganese-nitrogen doped carbon material (Mn-NC material);

[0010] (4) mixing the Mn-NC material obtained in step (3) and the Ni-CDs in step (2) with water, stirring and ultrasonically treating the mixture, and then freeze-drying the mixture to obtain a nickel-manganese modified carbon-based assembly material (Mn-NC@Ni-CDs material);

[0011] According to the above scheme, in step (1), the concentration of lignin in solvent water is 150-200 g / L; the volume ratio of nitric acid to water is 1:(5-7), and the mass fraction of nitric acid is 60%-70%; the ultrasonic treatment time is 4-6 h; and the deionized water is washed to a pH of 6.5-7.5.

[0012] According to the above scheme, in step (2), the mass ratio of lignin treated with nitric acid to nickel chloride hexahydrate is 1:(0.1-0.3), and the volume ratio of the total mass of lignin treated with nitric acid and nickel chloride hexahydrate to water is (1-2) g:100 mL; the hydrothermal reaction temperature is 160-200° C., and the reaction time is 3-8 h.

[0013] According to the above scheme, in step (2), the filtrate is dialyzed using a dialysis bag with a molecular weight of 2000 to 4000 for 24 to 60 hours; the freeze-drying temperature is -40 to -60°C; the filter residue is dried at 50 to 70°C for 4 to 6 hours.

[0014] According to the above scheme, the nickel-doped carbon dots obtained in step (2) are cyan fluorescent nickel-doped carbon dots, which have good fluorescence properties and photostability, and have a high fluorescence intensity near the wavelength of 400-550nm under the excitation of ultraviolet light of 330-420nm.

[0015] According to the above scheme, the specific process of step (3) is as follows: the filter residue obtained in step (2), manganese sulfate monohydrate and water are mixed and stirred for 2 to 4 hours to form solution A; cyanuric acid, melamine and water are stirred for 2 to 4 hours to form solution B; then solution A and solution B are mixed and stirred for 7 to 9 hours, and then a hydrothermal reaction is carried out at a reaction temperature of 180 to 220° C. and a reaction time of 10 to 15 hours; wherein, in solution A, the filter residue obtained in step (2) and manganese sulfate monohydrate are added at a concentration of 2 to 3 g / L; and in solution B, the concentrations of cyanuric acid and melamine are added at a concentration of 25 to 40 g / L.

[0016] According to the above scheme, in step (3), the carbonization temperature is 750-850°C, the time is 1-3h, the temperature is increased to the carbonization treatment temperature at a heating rate of 5-10°C / min, and the carbonization instrument is a tubular carbonization furnace. This carbonization condition is simple to operate, effectively controls the heating rate, and reduces process energy consumption while ensuring effective carbonization.

[0017] According to the above scheme, in step (4), the concentration of nickel-doped carbon dots in solvent water is 50-300 mg / L, and preferably the concentration of nickel-doped carbon dots in water is 100-200 mg / L; the concentration of Mn-NC material in water is 5-20 g / L; the stirring time is 8-15 h; and the ultrasonic time is 0.5-2 h.

[0018] The nickel-manganese modified carbon-based assembly material (Mn-NC@Ni-CDs material) prepared by the above method of the present invention can be used in aqueous zinc ion batteries. The specific application method is: using the Mn-NC@Ni-CDs material as the positive electrode, the negative electrode as a zinc sheet, and the electrolyte as a zinc sulfate solution to assemble an aqueous zinc ion battery.

[0019] The present invention uses lignin as a carbon source, nitric acid as a catalyst to crack lignin and also as a nitrogen source, nickel chloride hexahydrate as a nickel source, and water as a solvent. After lignin is treated with nitric acid, the filtrate obtained by hydrothermal reaction is a nickel-doped carbon point solution (Ni-CDs), and the filter residue is subsequently doped with manganese and nitrogen and then carbonized at high temperature to convert it into Mn-NC carbon material. Finally, Ni-CDs are loaded onto the Mn-NC material through ultrasonic treatment to obtain a nickel-manganese modified carbon-based assembly material, which can be used in aqueous zinc ion batteries. Compared with the prior art, the above technical scheme conceived by the present invention can achieve the following beneficial effects:

[0020] (1) The present invention uses lignin as a raw material, which solves the problem of limited raw material sources for preparing fluorescent carbon dots in the prior art. Nitrogen doping of carbon dots is achieved through preliminary treatment with nitric acid, followed by metal nickel doping through a hydrothermal reaction, and then combined with simple and easy methods such as dialysis filtration to obtain fluorescent carbon dots; in particular, the use of nickel source nickel chloride hexahydrate changes the gap of the electronic structure of Ni-CDs, thereby improving the photoluminescence and fluorescence quantum yield of Ni-CDs, which is a simple method for adjusting and optimizing the optical properties of carbon dots.

[0021] (2) The nickel-doped carbon dots prepared by the present invention have good fluorescence properties and biocompatibility, low cost, low toxicity, and good electronic conductivity. On this basis, the nickel-manganese modified carbon-based assembly material prepared by composite Mn-NC carbon material has good electronic conductivity and abundant active sites, which solves the problems of low conductivity, poor stability, and high cost of single carbon materials.

[0022] (3) Compared with traditional carbon materials, the nickel-manganese modified carbon-based assembly material prepared by the present invention has excellent electrochemical properties and can be used in aqueous zinc ion batteries. Specifically, the assembled aqueous zinc ion battery provides excellent specific capacitance at a current density of 1A / g, and has high power density and energy density.

[0023] (4) The nickel-manganese modified carbon-based assembly material prepared by the present invention is environmentally friendly and can be used in aqueous zinc ion batteries to alleviate the dilemma of battery recycling to a certain extent, which is beneficial to environmental protection and solves the problem of low energy density and power density of energy storage materials. In addition, the present invention utilizes lignin to the greatest extent in terms of raw material utilization, and the filter residue and filtrate of the raw materials are fully utilized to solve the current limitations in the application of lignin. BRIEF DESCRIPTION OF THE DRAWINGS

[0024] Figure 1 1 is a fluorescence spectrum of the nickel-doped carbon dots prepared in Example 1 at different excitation wavelengths.

[0025] Figure 2 This is a transmission electron microscopy (TEM) image of the nickel-doped carbon dots prepared in Example 1.

[0026] Figure 3 This is an X-ray photoelectron spectroscopy analysis chart (XPS) of the nickel-doped carbon dots prepared in Example 1.

[0027] Figure 4 This is the adsorption-desorption isotherm and pore size distribution of the Mn-NC@Ni-CDs material prepared in Example 1 (inset).

[0028] Figure 5 This is the EDS characterization spectrum of the Mn-NC@Ni-CDs material prepared in Example 1.

[0029] Figure 6 This is the battery cycle diagram of the assembled zinc ion battery of the Mn-NC@Ni-CDs material prepared in Example 1. DETAILED DESCRIPTION

[0030] In order to better understand the present invention, the content of the present invention is further explained below in conjunction with the embodiments, but the present invention is not limited to the following embodiments.

[0031] Example 1

[0032] A method for preparing a nickel-manganese modified carbon-based assembly material based on lignin, specifically comprising the following steps:

[0033] (1) 15 g of lignin was added to 90 mL of water, stirred for 0.5 h, and then 15 mL of nitric acid (mass fraction 68%) was added dropwise under continuous stirring and continued to stir for 0.5 h, followed by ultrasonic treatment for 6 h; the solution was filtered and washed with deionized water until neutral, and freeze-dried at -50 ° C to obtain nitric acid-treated lignin (about 9 g);

[0034] (2) 1 g of the lignin treated with nitric acid obtained in step (1) was mixed with 0.2 g of nickel chloride hexahydrate and dispersed in 100 mL of deionized water. The mixture was stirred for 10 min and then ultrasonicated for 25 min. The mixture was transferred to a reactor and hydrothermaled at 180° C. for 4 h. The filtrate was filtered to remove insoluble matter. The filtrate was dialyzed for 24 h using a 3000 MW molecular weight dialysis bag and then freeze-dried at -50° C. to obtain Ni-CDs (about 80 mg). The residue was dried for standby use at a drying temperature of 60° C. for 5 h.

[0035] (3) 1 g of the above-mentioned filter residue and 1 g of manganese sulfate monohydrate were mixed and dispersed in 40 mL of deionized water and stirred for 2 h to form a solution A; at the same time, 6.31 g of melamine and 6.45 g of cyanuric acid were mixed and dispersed in 20 mL of deionized water and stirred for 2 h to form a solution B; then, solution A and solution B were mixed and stirred for 8 h, and the resulting mixture was subjected to a hydrothermal reaction at 200 ° C for 12 h to achieve manganese doping. After drying, it was transferred to a tubular carbonization furnace and carbonized at 800 ° C for 2 h to obtain a Mn-NC material;

[0036] (4) Take 3 mg of Ni-CDs obtained in step (2) and 200 mg of Mn-NC material and mix them in 20 mL of water, stir for 12 h, then ultrasonically treat for 1 h, and then freeze-dry for 24 h to obtain a nickel-manganese modified carbon-based assembly material (wherein the mass of Ni-CDs is 1.5% of the Mn-NC material, marked as Mn-NC@1.5%Ni-CDs material).

[0037] like Figure 1As shown, the nickel-doped carbon dots (Ni-CDs) prepared in Example 1 have significant fluorescence characteristics under ultraviolet excitation wavelengths of 330 to 420 nm, and have a higher fluorescence intensity near a wavelength of 477 nm.

[0038] like Figure 2 and Figure 3 As shown, the nickel-doped carbon dots prepared in Example 1 have uniform size distribution, good dispersion and no obvious agglomeration phenomenon; and the nickel element is successfully doped to obtain nickel-doped carbon dots with a larger emission wavelength.

[0039] like Figure 4 and Figure 5 As shown, the EDS characterization spectrum shows that Mn, Ni, C, N, O and other elements are uniformly distributed on the synthesized Mn-NC@Ni-CDs material, indicating that Ni-CDs are successfully loaded on the Mn-NC material, that is, the nickel-manganese modified carbon-based assembly material is successfully prepared; through the N2 adsorption-desorption isotherm and pore size distribution, it is concluded that the Mn-NC@Ni-CDs material exhibits a type IV isotherm with a typical hysteresis loop, and the average particle size is about 14.46nm, indicating that the material has a mesoporous structure.

[0040] Application Example 1

[0041] Figure 6 This is a cycle diagram of an aqueous zinc ion battery assembled with the Mn-NC@Ni-CDs material (i.e., Mn-NC@1.5% Ni-CDs material) prepared in Example 1. The Mn-NC@Ni-CDs material prepared in Example 1 is used in an aqueous zinc ion battery. The specific application method is: using the Mn-NC@Ni-CDs material as the positive electrode, the negative electrode as a zinc sheet, and the electrolyte as a 2M zinc sulfate solution to assemble an aqueous zinc ion battery. Figure 6 From the battery cycle curve, it can be seen that after 5000 cycles at 10A / g, the capacity retention rate is above 90%, and the coulombic efficiency is close to 100%, indicating that this aqueous zinc-ion battery has excellent energy storage performance such as stable operating voltage, high battery capacity and long life.

[0042] After the aqueous zinc-ion battery was left to stand overnight, its electrochemical performance was tested using an electrochemical workstation. The aqueous zinc-ion battery provided an excellent specific capacitance of 195F / g at a current density of 1A / g, and an energy density of 156Wh / kg at a power density of 1200W / kg.

[0043] Comparative Example

[0044] In this comparative example, the Mn-NC material prepared in step (3) of Example 1 replaces the Mn-NC@Ni-CDs material in Application Example 1, and the rest is the same as Application Example 1. The results of the performance test are as follows: the aqueous zinc ion battery provides a specific capacitance of 121.33 F / g at a current density of 1 A / g, and an energy density of 96.9 Wh / kg when the power density is 1200 W / kg.

[0045] Compared with Application Example 1, the specific capacitance of the zinc ion battery assembled using Mn-NC material in this comparative example at a current density of 1A / g decreased by 73.67F / g, and the energy density decreased by 59.1Wh / kg, indicating that in the nickel-manganese modified carbon-based assembly material described in the present invention, the introduction of Ni-CDs improves the electronic conductivity of the Mn-NC material, thereby improving the electrochemical properties of the assembly material, providing a new perspective for obtaining zinc ion batteries with high energy and power density.

[0046] Example 2

[0047] The difference between Example 2 and Example 1 is that the mass of Ni-CDs in step 4 is 1% of that of Mn-NC material, and the other steps are the same as those in Example 1. The nickel-manganese modified carbon-based assembly material finally prepared in Example 2 is marked as Mn-NC@1%Ni-CDs material.

[0048] The Mn-NC@1%Ni-CDs material in Example 2 was used to replace the Mn-NC@1.5%Ni-CDs material in Application Example 1, and the rest was the same as in Application Example 1. The results of the performance test were as follows: the aqueous zinc ion battery provided an excellent specific capacitance of 152.79F / g at a current density of 1A / g, and an energy density of 122.24Wh / kg when the power density was 1200W / kg.

[0049] Example 3

[0050] The only difference between Example 3 and Example 1 is that the mass of Ni-CDs in step 4 is 2% of the Mn-NC material, and the other steps are the same as Example 1. The nickel-manganese modified carbon-based assembly material finally prepared in Example 3 is marked as Mn-NC@2%Ni-CDs material.

[0051] The Mn-NC@2%Ni-CDs material of Example 3 was used to replace the Mn-NC@1.5%Ni-CDs material in Application Example 1, and the rest was the same as Application Example 1. The results of the performance test are as follows: the aqueous zinc ion battery provides an excellent specific capacitance of 176.55F / g at a current density of 1A / g, and an energy density of 141.24Wh / kg when the power density is 1200W / kg.

[0052] Those skilled in the art will readily appreciate that the above are merely preferred embodiments of the present invention and do not limit the present invention. Any modifications, equivalent substitutions, etc. made within the spirit and principles of the present invention are within the protection scope of the present invention.

Claims

1. A method for preparing a nickel-manganese modified carbon-based assembly material based on lignin, characterized in that: The steps include: (1) mixing lignin with solvent water, then dropping nitric acid into the mixture and mixing, ultrasonically treating, filtering, washing, and freeze-drying to obtain nitric acid-treated lignin; (2) mixing the lignin treated with nitric acid obtained in step (1) and nickel chloride hexahydrate with solvent water, and then performing a hydrothermal reaction; after the hydrothermal reaction is completed, performing solid-liquid separation to obtain a filtrate and a filter residue; filtering the filtrate to remove insoluble matter, dialyzing, and freeze-drying to obtain nickel-doped carbon dots; and drying the filter residue for standby use; (3) mixing the filter residue obtained in step (2) with cyanuric acid, melamine, manganese sulfate monohydrate and water, and performing a hydrothermal reaction to achieve metallic manganese doping. After the reaction is completed, the solid is collected, dried and then moved to a tubular furnace for carbonization treatment to obtain a manganese-nitrogen doped carbon material; (4) The manganese-nitrogen doped carbon material obtained in step (3) and the nickel-doped carbon dots obtained in step (2) are mixed with water, stirred and ultrasonically treated, and then freeze-dried to obtain a nickel-doped carbon dot composite manganese-nitrogen doped carbon material, i.e., a nickel-manganese modified carbon-based assembly material.

2. The method for preparing a nickel-manganese modified carbon-based assembly material based on lignin according to claim 1, characterized in that: In step (1), the concentration of lignin added to the solvent water is 150-200 g / L, the volume ratio of nitric acid to water is 1:(5-7), the mass fraction of nitric acid is 60%-70%; the ultrasonic treatment time is 4-6 hours; and the deionized water is washed to a pH of 6.5-7.

5.

3. The method for preparing a nickel-manganese modified carbon-based assembly material based on lignin according to claim 1, characterized in that: In step (2), the mass ratio of the lignin treated with nitric acid to nickel chloride hexahydrate is 1:(0.1-0.3), the volume ratio of the total mass of the lignin treated with nitric acid and nickel chloride hexahydrate to water is (1-2) g:100 mL; the temperature of the hydrothermal reaction is 160-200° C., and the time is 3-8 h.

4. The method for preparing a nickel-manganese modified carbon-based assembly material based on lignin according to claim 1, characterized in that: In step (2), the filtrate is dialyzed using a dialysis bag with a molecular weight of 2000 to 4000 for 24 to 60 hours; the freeze-drying temperature is -40 to -60°C; the filter residue is dried at a temperature of 50 to 70°C for 4 to 6 hours.

5. The method for preparing a nickel-manganese modified carbon-based assembly material based on lignin according to claim 1, characterized in that: The nickel-doped carbon dots obtained in step (2) are cyan fluorescent nickel-doped carbon dots, which have a characteristic fluorescence peak in the wavelength range of 400 to 550 nm under the excitation of ultraviolet light with a wavelength of 330 to 420 nm.

6. The method for preparing a nickel-manganese modified carbon-based assembly material based on lignin according to claim 1, characterized in that: The specific process of step (3) is as follows: the filter residue obtained in step (2), manganese sulfate monohydrate and water are mixed and stirred for 2 to 4 hours to form a solution A; cyanuric acid, melamine and water are stirred for 2 to 4 hours to form a solution B; then the solution A and the solution B are mixed and stirred for 7 to 9 hours, and then a hydrothermal reaction is carried out at a reaction temperature of 180 to 220° C. and a reaction time of 10 to 15 hours; wherein, in the solution A, the filter residue obtained in step (2) and manganese sulfate monohydrate are added at a concentration of 2 to 3 g / L; in the solution B, the concentrations of cyanuric acid and melamine are added at a concentration of 25 to 40 g / L; and the volume ratio of the solution A to the solution B is 1:(0.3 to 0.7).

7. The method for preparing a nickel-manganese modified carbon-based assembly material based on lignin according to claim 1, characterized in that: In step (3), when the carbonization treatment is carried out in a tubular furnace, the temperature of the carbonization treatment is 750-850° C., the time is 1-3 hours, and the temperature is increased to the carbonization treatment temperature at a heating rate of 5-10° C. / min.

8. The method for preparing a nickel-manganese modified carbon-based assembly material based on lignin according to claim 1, characterized in that: In step (4), the concentration of nickel-doped carbon dots added to water is 50-300 mg / L, the concentration of manganese-nitrogen-doped carbon materials added to water is 5-20 g / L, the stirring time is 8-15 h, and the ultrasonic time is 0.5-2 h.

9. Use of the nickel-manganese modified carbon-based assembly material prepared by any method of claims 1 to 8 as a positive electrode of an aqueous zinc ion battery.

10. The use according to claim 9, characterized in that: The specific application method is: using the nickel-manganese modified carbon-based assembly material as the positive electrode, the zinc sheet as the negative electrode, and the zinc sulfate solution as the electrolyte to assemble a button cell, thereby obtaining an aqueous zinc ion battery.